Distributional impacts of the 2008 global food price spike in Vietnam - Andy McKay; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Agriculture and food cultivation production remains a key sector in the Vietnamese economy in terms of productive activities, income generation, and national export earnings. Higher world market prices should therefore in principle have a beneficial impact on rural farmers. This is based however on the assumption that world prices are transmitted and that farmers have the capacity to respond. In addition, many poorer farm households may be net consumers. Using data from the Vietnam Access to Resources Household Survey (VARHS) and the Vietnam Household Living Standard Survey (VHLSS) combined with available macro-data, this paper investigates how global price changes appear to have impacted on rural welfare in Vietnam during 2006-12. In this paper we study the case of rice in Vietnam, in the context of the 2008 food price spike. We analyse the responses of domestic producer and consumer prices, and discuss the policy actions taken by the government to help reduce the impact on consumers, as well as to continue to encourage production. We also look at the distributional impact of the resulting domestic price changes, using data from a specialist rural household survey to look at production response. Vietnam was effective in taking policy actions to limit the extent of transmission of the world price changes; and more poorer households benefitted from the price increase than lost.
Keywords: O1; O5; Q18; 330; food prices; rice; Vietnam; transmission